IMPLEMENTASI ALGORITMA KONVERSI CITRA KE POLA KARAWO PADA APLIKASI MOBILE BERBASIS FLUTTER - Wati, Nursetia; Utina, Sunarti Dwi Putra (Jurnal Technopreneur (JTech), 2025)
This study aims to implement an image-to-Karawo pattern conversion algorithm in a Flutter-based mobile application as part of the digitalization effort within Gorontalo’s creative industry. The system integrates several image processing stages, including preprocessing, adaptive thresholding, color clustering, edge simplification, and grid generation to produce Karawo patterns ready for embroidery reference. The development method includes interface design, algorithm implementation, and the integration of editing features such as brush tools, dynamic color selection, noise removal, line-thickness adjustment, and undo–redo functionality. The evaluation was performed using various input images—such as floral and human objects—to assess shape accuracy, edge clarity, and color-reduction capability. The results show that the application successfully preserves the main visual structure, produces consistent patterns, and provides editing flexibility that previous software did not support. In conclusion, the implementation of the image conversion algorithm in this mobile application effectively improves the efficiency of Karawo pattern design and offers a potential digital solution for culturally rooted fashion industries.